Increasing success and evolving barriers in the hepatitis C cascade of care during the direct acting antiviral era. - Autumn Zuckerman; Andrew Douglas; Sam Nwosu; Leena Choi; Cody Chastain (PLoS ONE)
Barriers remain in the hepatitis C virus (HCV) cascade of care (CoC), limiting the overall impact of direct acting antivirals. This study examines movement between the stages of the HCV CoC and identifies reasons why patients and specific patient populations fail to advance through care in a real world population. We performed a single-center, ambispective cohort study of patients receiving care in an outpatient infectious diseases clinic between October 2015 and September 2016. Patients were followed from treatment referral through sustained virologic response. Univariate and multivariate analyses were performed to identify factors related to completion of each step of the CoC. Of 187 patients meeting inclusion criteria, 120 (64%) completed an evaluation for HCV treatment, 119 (64%) were prescribed treatment, 114 (61%) were approved for treatment, 113 (60%) initiated treatment, 107 (57%) completed treatment, and 100 (53%) achieved a sustained virologic response. In univariate and multivariate analyses, patients with Medicaid insurance were less likely to complete an evaluation and were less likely to be approved for treatment. Treatment completion and SVR rates are much improved from historical CoC reports. However, linkage to care following referral continues to be a formidable challenge for the HCV CoC in the DAA era. Ongoing efforts should focus on linkage to care to capitalize on DAA treatment advances and improving access for patients with Medicaid insurance.